The Passive Defense and Sustainable Development with Emphasis on Threat Ridden Land Uses of Tabriz, as a Metropolitan city, in Terms of War - Karim Husseinzadeh Dalir; Kiumars Maleki; Arezo Shafaati; Mohammad Rauf Heidarifar (جغرافیا و پایداری محیط)
The alteration of land uses based on defense and security issues, concentrating on the principles of passive defense, and getting benefited from the experiences of the pioneering countries in this regards could be very influential in sustainable and secure urban planning and development. Due to the military achievements in the developed countries, we must take steps to secure our cities so that they suffer least life and financial casualties and costs during wartime. This article tries to apply the principles of passive defense in urban planning especially in sensitive and installation land uses as the threatened land uses and in defending human beings and preserving their settlements and ,consequently providing the cities with a safer space. In this study we have made use of GIS to determine the diffusion and position of strategic land uses in this old historic city located in the North West of the country. As the outcome of this research, central parts and the south and northwestern areas were identified as the most risky and unreliable places in terms of passive defense related issues.